Strategy of Increasing Food Security based on Macro and Micro Aspects - Widayaningsih, Neni; Barokatuminalloh, Barokatuminalloh (JEJAK: Jurnal Ekonomi dan Kebijakan, 2016)
The preliminary studies that have been conducted show that the food availability in 27 districts in Banyumas Regency on average is still low. The purpose of this research is to formulate of a strategy to improve the food security by synergizing the macro and micro aspects. The method used is the tabulation analysis, IFE and EFE Matrix, and also IE Matrix. The IE matrix shows the food security based on the macro and micro aspects that are in the first cell, which means that the food security conditions are experiencing the growing and buliding. The strategies of improving the food security from the micro and macro aspects are first, to develop the food production in accordance with the potential and comodities of the excellent food in accordance with the specializations of regions (districts). Second, it requires a partnership and a cooperation of distributing the excellent food production. Third, the investment is required to improve the diversification of food. Fourth, it requires the cooperation between the farmers and the government agencies concerned with the development, supply and service of excellent means of agricultural production with supervision and increased credit services. Fifth, the off-farm activities should be developed by forming the cooperatives or the small and household businesses on the basis of farming activities. Besides, in order to meet the consumption of food that is safe, qualified, and nutritious, it is necessary to increase the knowledge and awareness about the food security at the household level by empowering the cooperatives or small and household businesses by utilizing Dasa Wisma group, PKK, Majelis Talim, and other non-governmental groups.